2021
DOI: 10.3390/molecules26092593
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Properties of the NSAID Drug Naproxen Targeting the Nucleoprotein of SARS-CoV-2 Coronavirus

Abstract: There is an urgent need for specific antiviral treatments directed against SARS-CoV-2 to prevent the most severe forms of COVID-19. By drug repurposing, affordable therapeutics could be supplied worldwide in the present pandemic context. Targeting the nucleoprotein N of the SARS-CoV-2 coronavirus could be a strategy to impede viral replication and possibly other essential functions associated with viral N. The antiviral properties of naproxen, a non-steroidal anti-inflammatory drug (NSAID) that was previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 48 publications
2
49
0
1
Order By: Relevance
“…Naproxen has antiviral and anti-inflammatory effects. It inhibted replication of SARS-CoV-2 and protected against virus-induced damage pulmonary epithelium in vitro [85] . Clinical trials were conducted to study the safety and efficacy of Fostamatinib, Acalabrutinib, Ibrutinib, and Bevacizumab, Alteplase, Aspirin, and Naproxen for hospitalized patients with COVID-19 ( ClinicalTrials.gov ) (NCT04579393-NCT04497948-NCT04375397-NCT04275414 -NCT04357730-NCT04365309- NCT04325633 ).…”
Section: Discussionmentioning
confidence: 98%
“…Naproxen has antiviral and anti-inflammatory effects. It inhibted replication of SARS-CoV-2 and protected against virus-induced damage pulmonary epithelium in vitro [85] . Clinical trials were conducted to study the safety and efficacy of Fostamatinib, Acalabrutinib, Ibrutinib, and Bevacizumab, Alteplase, Aspirin, and Naproxen for hospitalized patients with COVID-19 ( ClinicalTrials.gov ) (NCT04579393-NCT04497948-NCT04375397-NCT04275414 -NCT04357730-NCT04365309- NCT04325633 ).…”
Section: Discussionmentioning
confidence: 98%
“…Due to the severity of the global health pandemic caused by COVID-19, discovering the drugs capable of inhibiting SARS-CoV-2 can be considered as a therapeutic target in the COVID treatment. In this regard, repurposing FDA-approved drugs, such as NSAIDs against COVID-19, can provide therapeutic alternatives which can be used as an effective, safe treatment for COVID-19 [ 12 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some recent papers have studied the antiviral activity of NSAIDs against SARS-CoV-2 protein. For example, they showed that the anti-viral activity of Ketotifen, Indomethacin, and Naproxen could reduce SARS-CoV-2 replication [ [10] , [11] , [12] ]. Furthermore, it was shown that indomethacin exerts anti-SARS-CoV activity in both in vivo and in vitro models [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Celecoxib, at concentrations not clinically achievable (50 microM), inhibits the main protease of SARS-CoV-2, M-pro, in vitro ( Gimeno et al, 2020 ), but the effect on viral entry or replication was not assessed. Naproxen prevented SARS-CoV-2 nucleoprotein oligomerization by binding its N-terminal domain and inhibited viral replication in VERO E6 cells and reconstituted human pulmonary epithelium ( Terrier et al, 2021 ). In silico analyses of publicly available transcriptomic databases of rat kidney tissues treated with multiple NSAIDs in vivo found modulated expression of receptors for SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%